Percutaneous delivery of self-propelling hemostatic powder for managing non-compressible abdominal hemorrhage: a proof-of-concept study in swine. Issue 5 (May 2022) - Cau, Massimo F.; Ali-Mohamad, Nabil; Baylis, James R.; Zenova, Veronika; Khavari, Adele; Peng, Nuoya; McFadden, Andrew; Donnellan, Fergal; Owen, Daniel R.; Schaeffer, David F.; Nagaswami, Chandrasekaran; Litvinov, Rustem I.; et al.
Highlights: Non-compressible intra-abdominal hemorrhage (NCIAH) is a major cause of preventable death in trauma, and can only be managed surgically. Safety and efficacy of hemostatic powder (SPTP) that self-propels through pooled blood within the abdomen was tested in a swine model of NCIAH. Spray system developed to deliver SPTP into the abdomen through a minimally invasive procedure. Animals receiving SPTP showed a trend toward increased survival versus animals receiving standard of care fluid resuscitation. Demonstrates proof-of-concept of SPTP delivery as a new potential strategy for managing NCIAH. Abstract: Introduction: Non-compressible intra-abdominal hemorrhage (NCIAH) is a major cause of preventable death on the battlefield and in civilian trauma. Currently, it can only be definitively managed with surgery, as there are limited strategies for controlling ongoing NCIAH in the prehospital environment. We hypothesized that a self-propelling thrombin-containing powder (SPTP) could increase survival in a swine model of NCIAH when delivered percutaneously into the closed abdomen using an engineered spray system. Materials and Methods: Nineteen swine underwent surgical laparotomy followed by a Grade V liver injury that created massive hemorrhage, before closing the abdomen with sutures. Animals either received treatment with standard of care fluid resuscitation (n=9) or the SPTP spray system (n=10), which consisted of a spray device and a 14 Fr catheter. Using the spray system, SPTP was delivered into a hemoperitoneum identified using a focused assessment with sonography in trauma (FAST) exam. Lactated Ringer's solution was administered to all animals to maintain a mean arterial pressure (MAP) of >50 mmHg. The primary outcome was percentage of animals surviving at three hours following injury. Results: In the swine model of NCIAH, a greater percentage of animals receiving SPTP survived to three hours, although differences were not significant. The SPTP spray system increased the median survival of animals from 1.6 hr in the fluid resuscitation group to 4.3 hr. The SPTP spray system delivered a total mass of 18.5 ± 1.0 g of SPTP. The mean change in intra-abdominal pressure following SPTP delivery was 5.2 ± 1.8 mmHg (mean ± SEM). The intervention time was 6.7 ± 1.7 min. No adverse effects related to the SPTP formulation or the spray system were observed. SPTP was especially beneficial in animals that had either severely elevated lactate concentrations or low mean arterial pressure of <35 mmHg shortly after injury. Conclusions: This demonstrates proof-of-concept for use of a new minimally invasive procedure for managing NCIAH, which could extend survival time to enable patients to reach definitive surgical care.